2021
DOI: 10.1186/s40104-021-00581-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids can improve lipid and glucose metabolism independently of the pig gut microbiota

Abstract: Background Previous studies have shown that exogenous short-chain fatty acids (SCFAs) introduction attenuated the body fat deposition in conventional mice and pigs. However, limited studies have evaluated the effects of exogenously introduced SCFAs on the lipid and glucose metabolism independently of the gut microbiota. This study was to investigate the effects of exogenous introduction of SCFAs on the lipid and glucose metabolism in a germ-free (GF) pig model. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 69 publications
1
24
0
1
Order By: Relevance
“…To overcome this impairment several nutritional strategies have been developed [ 1 , 19 ]. These include supplementations with colostrum [ 20 ] or bovine whey protein [ 21 ], nucleotides [ 22 ], short-chain fatty acids [ 23 ] and specific amino acids ( AA ) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this impairment several nutritional strategies have been developed [ 1 , 19 ]. These include supplementations with colostrum [ 20 ] or bovine whey protein [ 21 ], nucleotides [ 22 ], short-chain fatty acids [ 23 ] and specific amino acids ( AA ) [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear how Christensenellaceae is involved in the hyperglycemic status. One possible mechanism is that Christensenellaceae can produce short-chain fatty acids, which are known to reduce the risk of diabetes by various mechanisms, for example, increased insulin sensitivity and suppression of appetite ( Lau and Vaziri, 2019 ; Waters and Ley, 2019 ; Zhou et al., 2021 ). Additionally, inflammation has been considered one of the causes of both type 1 and type 2 diabetes ( Tsalamandris et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPR41 and GRP43 are understood to stimulate GLP-1 and PYY secretion and increase insulin-mediated glucose uptake in skeletal muscle ( Canfora et al, 2015 ). In vivo studies have demonstrated improvements in insulin sensitivity, mitochondrial biogenesis and function, reduced adiposity, and an increase in type I muscle fiber composition following SCFA administration ( Fushimi et al, 2001 ; Gao et al, 2009 ; Hong et al, 2016 ; Zhou et al, 2021 ) that correspond with an increased myoglobin expression ( Yamashita et al, 2014 ; Maruta et al, 2016 ; Figure 2 ). Accordingly, germ-free mice supplemented with SCFA were shown to exhibit greater muscle (gastrocnemius) mass and strength compared to germ-free controls ( Lahiri et al, 2019 ).…”
Section: Microbiome-centric Dietary Strategies To Counter Anabolic Resistancementioning
confidence: 99%